Periodontal health and salivary Interleukin -6 among preterm postpartum women - Dhamiaa M Mohammed-Salih; Wesal A Al-Obaidi (College of Dentistry/ University of Baghdad, 2014)
Background: Hormonal changes during pregnancy have been suggested to predispose women to gingivitis. Furthermore, advance periodontal infection in pregnant women may pose a threat to the placenta and uterus and may increase the like hood of preterm delivery. The aim of this study was to investigate the effect of salivary interleukin -6 (IL-6) level and periodontal health among preterm postpartum women. Materials and Methods: Salivary samples were taken from 33 preterm postpartum women (study group) and 33 full term postpartum women (control group). The supernatant salivary samples were assayed using atomic absorption spectrophotometer. Plaque, calculus and gingival indices were used for recording the oral hygiene and gingivitis also probing pocket depth was recorded. Results: The mean values of plaque index, calculus index probing pocket depth were higher among study group than control group with no statistically significant difference, but a highly significant difference was observed in the mean value of GI between the two groups. The full term women had a higher mean value of salivary IL-6 than study group with no statistically significant difference, weak positive correlation was found between salivary IL-6 and probing pocket depth in control group. On the other hand, weak negative correlations were noticed between salivary IL-6 among study group with Plaque index, Gingival index, Calculus index and probing pocket depth, also between salivary IL-6 with PlI, GI and CalI among control group. However, statistically all correlations were not significant. Conclusion: It is concluded that pregnant women during pregnancy required preventive programs directed for improvement of oral health and especially periodontal disease to prevent any pregnancy outcomes such as preterm delivery.